Quantitative assessment of S. mutans and C. albicans in patients with Haas and Hyrax expanders - Matheus Melo Pithon; Rogério Lacerda dos Santos; Wagner Sales Alviano; Antonio Carlos de Oliveira Ruellas; Mônica Tirre de Souza Araújo (Dental Press Editora, 2012)
OBJECTIVE: To assess and compare the number of Streptococcus mutans and Candida albicans colonies in patients with Haas and Hyrax appliances before and after insertion. METHODS: The sample consisted of 84 patients requiring orthodontic treatment. For all patients a midpalatal suture expansion was indicated. Patients were randomly divided into Group HA, who used the Haas appliance (n = 42) and Group HY, who used the Hyrax appliance (n = 42). Initially and thirty days after appliance insertion all patients were submitted to saliva collections. The saliva was diluted followed by seeding in Mitis Salivarius and CHROMagar media, for growth of S. mutans and C. albicans respectively. RESULTS: Results showed statistically significant difference between groups HA and HY for Streptococcus mutans and Candida albicans (p <0.05). Haas appliance promoted greater S. mutans and C. albicans proliferation when compared to Hyrax appliance. CONCLUSION: The Haas appliance favored greater proliferation of S. mutans and C. albicans when compared with the Hyrax appliance. Insertion of the appliances resulted in greater buildup of microorganisms.